Corak Pendidikan Kader Muhammadiyah Tahun 2005-2015 - Suparmun, Arifah Cahyo Andini; , Dr. Mohamad Ali, M.Pd (2016)
Since its inception the Muhammadiyah cadres have placed education as the programs and activities of strategic importance in order to prepare the cadres who have the human resources (HR) is a superior, competitive, have faith and monotheism formidable ideology, as well as solidarity and solidarity is strong. All of it was intended to Muhammadiyah ready to face the challenges of today's world and the future. This study aimed to describe the dynamics and the style of education cadre of Muhammadiyah Din Syamsuddin era. Data collection techniques in this research were interviews (in-depth), the collection of documents and triangulation. The analysis used in this study is a qualitative research approach is descriptive analytic research methods typically examine the objective conditions that nature in which researchers act as a key instrument. The data were analyzed inductively. The results of this study indicate that the dynamics of the education cadre of Muhammadiyah years 2005-2015 took place on an ongoing basic through revilatization cadres strategy and members of the structuring step, development, improvement, and development of core Muhammadiyah member. This can be achieved by estabilishment of ideological formulations (SPM 2007 and SPM 2015) as a response to the haziness, a shift of values, an identity crisis, and confidence in the life of leadership, cadre, and member of Muhammadiyah cadres education. After complexion tends 2005-2015 patterned progressive. This is evident from the pattern of development education cadre of Muhammadiyah system is flexible, open, free, and modificate with various developments in science and social conditions of society. But do not rule out other features to strengthen synergy at the Muhammadiyah cadres.